Characteristics and quality assessment of online mentoring profile texts in academic medical mentoring - Gernert, Jonathan A.; Warm, Maximilian; Salvermoser, Lukas; Krüger, Nils; Bethe, Stephan; Kocheise, Lorenz; von Hake, Malte; Meyer-Schwickerath, Charlotte; Graupe, Tanja; Fischer, Martin R.; Dimitriadis, Konstantinos (BMC medical education, 2023)
Background Mentoring is important for a successful career in academic medicine. In online matching processes, profile texts are decisive for the mentor-selection. We aimed to qualitatively characterize mentoring-profile-texts, identify differences in form and content and thus elements that promote selection. Methods In a mixed method study first, quality of texts in 150 selected mentoring profiles was evaluated (10-point Likert scale; 1 = insufficient to 10 = very good). Second, based on a thematic and content analysis approach of profile texts, categories and subcategories were defined. We compared the presence of the assigned categories between the 25% highest ranked profiles with the 25% lowest ranked ones. Finally, additional predefined categories ( hot topics ) were labelled on the selected texts and their impact on student evaluation was statistically examined. Results Students rated the quality of texts with a mean of 5.89 ± 1.45. 5 main thematic categories, 21 categories and a total of 74 subcategories were identified. Ten subcategories were significantly associated with high- and four with low-rated profiles. The presence of three or more hot topics in texts significantly correlated with a positive evaluation. Conclusion The introduced classification system helps to understand how mentoring profile texts are composed and which aspects are important for choosing a suited mentor.